Industrial brand equity: a systematic literature review and directions for future research - Fernando Rey Castillo-Villar; Enrique Murillo (Cogent Business & Management)
The importance of industrial brand equity in the business-to-business (B2B) marketplace has seen a considerable surge in the last decade, emphasizing its crucial role in shaping competitive advantages and fostering long-term relationships within industries. However, while research has thoroughly explored the concept of brand equity in the business-to-consumer (B2C) context and its various dimensions and implications for consumer behavior, research on industrial brand equity is still recent, with many aspects remaining underexplored and lacking comprehensive theoretical grounding. To advance this emerging and important domain, bibliometric analyses and the ‘Theory-Context-Characteristics-Methodology’ (TCCM) framework were applied as part of the systematic literature review. Overall, 64 articles from the Web of Science database, published between 2010 and 2023, were thoroughly reviewed and analyzed. The study offers a unifying overview of existing findings on industrial brand equity, systematically highlighting the most prominent theoretical perspectives, variables such as antecedents, mediators, moderators, and outcomes, as well as various contexts and research methods that have been employed in this area. Furthermore, it provides a future roadmap aimed at stimulating further studies on industrial brand equity, addressing gaps, and proposing new directions for research. Also provided are managerial implications suggested by the findings of this research.